Serum And Bone Marrow Prostatic Spe iafic Antigen And Pliostatic Acid PbQs:pbatase Levels In Patient’s With Prostatic Caueer - Hussein, Z. M.; Salman, M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Serum and hone marrow levels 0f ptostatic specific antigen a!ld prostatic acid phosphatase were- analyzed n .d q !antUIÂ·ed by Glottble antibody .raqioimrrumoa,ssay in 3.6 _prosÂ·tatic cance-r , patietllinc!udlng 2’3 with metaStatic c:anc.et. There was :a sÂ·i.gnÂ·ifl.co.m cotneJaÂ·,ion betwÂ¢enÂ· th.e ’Setl;liD a,n,d bope mat::tow: levels of JlrostaticÂ· Â·s, pecific antigen and prqstati’c acid pho phata.Se jndependently of the m.et ta:st;s (p< .QO: O 1 ).. Np pÂ·ath;nt Â·willprqsta,ticancer :and posiriY:e bohe .matrW pros.tatJc spec:ifk .an.tif?;en or p_rostati acid pbos:pbatase l vels lla:d QQnnaÂ·l serum level. Qwintl’fication of bone: marrow: ptostatit specific antigen and .prostati-c acid phosp’ha’t s"’dees.Jlot prov,id’e 1’);1Qre infgrmationÂ· thah. does s rum deterritination.